Revisiting Burns And Stalker: Formal Structure And New Venture Performance In Emerging Economic Sectors - Sine, Wesley D.; Mitsuhashi, Hitoshi; Kirsch, David A. (Academy of Management Journal, 2006)
This study examines the effects of formal structure on the performance of new ventures in the emergent Internet sector during the years 1996–2001. Burns and Stalker (1961) argued that in dynamic economic sectors, firms with organic structures are more effective than those with more mechanistic structures. We suggest this proposition does not hold for new ventures in turbulent, emergent economic sectors. Building on Stinchombe’s (1965) arguments concerning new ventures’ liability of newness, we hypothesize that new ventures with higher founding team formalization, specialization, and administrative intensity outperform those with more organic organizational structures. Results support these hypotheses.